E-Book Interaktif IPA Terintegrasi Potensi Lokal Kulon Progo: Tinjauan Kebutuhan Guru dan Peserta Didik - Yanarti; Heru Kuswanto; Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to analyze the needs of students and teachers for the development of interactive e-books that are integrated with the local potential of Kulon Progo. This research is qualitative research with a case study approach. Data collection uses needs analysis questionnaires, interviews and documentation. A needs analysis questionnaire was given to 156 students of SMPN 1 Nanggulan Kulon Progo. Interviews were conducted with two science teachers at SMPN 1 Nanggulan Kulon Progo. Interview and questionnaire data analysis techniques use qualitative descriptive. The results of this research are 1) aspects of the student learning process tend to be passive with varying student learning motivation; 2) aspects of using interactive learning media have never used interactive e-books for learning; 3) aspects of student characteristics in understanding concepts are still lacking, preferring to use smartphone media and practicums when learning; 4) the aspect of integrating science with the local potential of Kulon Progo has never been used in learning. Based on data analysis, it can be concluded that teachers and students need interactive e-books that are integrated with the local potential of Kulon Progo to support the learning process.